1999
DOI: 10.1021/la980921b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Support Effects on Bimetallic Pt−Ru Nanoparticles Formed from Molecular Precursors

Abstract: We describe the preparation, structural characterization, and support interactions experienced by two different compositions of Pt−Ru nanoparticles supported on several carbons (carbon black, fullerene soot, and desulfurized carbon black). The bimetallic nanoparticles, obtained by reduction of the neutral molecular precursors PtRu5C(CO)16 and Pt2Ru4(CO)18 (the latter of which lacks a central “stabilizing” carbide core) at elevated temperatures in a hydrogen atmosphere, show a structural homology, exhibiting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 43 publications
4
119
3
1
Order By: Relevance
“…(PPN) 2 [Ru 6 C(CO) 16 ] and (PPN) 2 [Ru 5 C(CO) 14 ] were synthesized as described previously. [19] [Pt(COD)Cl 2 ], [Au(PPh 3 )Cl] and H 2 CO were supplied by Sigma-Aldrich, H 2 NC 3 H 7 by Acros Organics, HPPh 2 by Fluka, and all were used as received.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(PPN) 2 [Ru 6 C(CO) 16 ] and (PPN) 2 [Ru 5 C(CO) 14 ] were synthesized as described previously. [19] [Pt(COD)Cl 2 ], [Au(PPh 3 )Cl] and H 2 CO were supplied by Sigma-Aldrich, H 2 NC 3 H 7 by Acros Organics, HPPh 2 by Fluka, and all were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Cluster 2, which is also known, [20] was prepared here by a new, easier route from (PPN) 2 [Ru 6 C(CO) 16 ] and Au(PPh 3 )Cl. Both clusters (Scheme 1) were unambiguously identified by their IR spectra.…”
Section: Anchoring and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CNT catalyst support could be an important factor affecting the catalyst activity due to metal-support interactions. In a previous study, fullerene soot and carbon black were found to have different interactions with the Pt/Ru catalysts [48] due to their different surface structures. Although the enhancement from the metal-carbon support interactions toward methanol electro-oxidation is not fully understood, we believe that the CNTs, which have a curved graphitic surface, could promote the PtRu activity.…”
Section: Potentiostatic Methanol Oxidation On Ptru/cntmentioning
confidence: 95%
“…The delicate control of composition, particle size, and dispersion state are only a few of the requirements for practical catalysts. The co-impregnation method [13][14][15][16][17][18][19][52][53][54][55][56][57][58][59][60][61] is a simple and effective method for the preparation of high surface area carbon supported electrocatalysts. We have shown that the structural properties and electrocatalysis of carbon supported PtRu nanoparticles 3 JCAT04-486 revised W. Sugimoto et al vary with the type of precursor employed, and the activity towards methanol electro-oxidation is sensitive to the pyrolysis temperature [14].…”
Section: Introductionmentioning
confidence: 99%